An Analysis of Illocutionary Acts of Hillary Clinton’s Concession Speech to Donald Trump in Presidential Election - Muhammad Hudri; irwandi Irwandi (Muhammadiyah University of Mataram, 2018)
Illocutionary Acts is what the speaker wants to achieve by uttering something, and illocutionary acts is an utterance which has a particular conventional force. About this, illocutionary acts in Hillary Clinton’s speech is interesting to be analyzed. The purpose of this research is to analyze the types of illocutionary acts found in Hillary Clinton’s concession speech to Donald Trump. The writer used descriptive qualitative research. The main research instrument was the writer herself supported by the data analysis sheet. The data analysis was performed by categorizing the data based on Searle’s categorization of speech acts (2005) which include assertive, directives, commissives, expressive and declarative speech acts. Each category was thoroughly observed to find the answer of the research questions. The final step was presenting the data and making a conclusion in reference to the findings of the research. The research findings show that the types of illocutionary acts found in Hillary Clinton’s concession speech to Donald Trump consist of assertives, directives, commissives, expressives and declaratives. Assertions have the highest frequency of occurrence 13 types (36.1%). It is followed by directives, commissives, expressives and declaratives which occur 9 types (25%), 3 types (8.3%), 9 types (25%) and 2 types (5.6%) respectively. The dominant illocutionary acts in Hillary Clinton’s speech are assertives. Assertation showed the highest frequency of assertives. So, the total of data were 36 types of illocutionary acts founds in Hillary Clinton’s concession speech to Donald Trump.